ANALISIS PENGARUH SANKSI DAN PENERTIBAN PAJAK KENDARAAN BERMOTOR TERHADAP EFEK JERA WAJIB PAJAK DENGAN WATAK WAJIB PAJAK SEBAGAI PEMODERASI - Muhammad Fachrul Syarlis; Putri Amanda Octavia (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
The purpose of this study is to determine the effect of tax sanctions and tax control on the deterrent effect of Motor Vehicle Taxpayers associated with taxpayer interaction (Study on UPT SAMSAT Revenue scope Office of South Sulawesi Province).Types of data used are: Primary data in the form of questionnaires and secondary data in the form of monthly realization report of Motor Vehicle Tax (PKB) fiscal year 2015-2017. Data analysis method used is Quantitative Analysis by using multiple linear analysis and Moderated Reggression Analysis (MRA), validity test, reability test, normality test and multicolinearity test. Population in this research is all Motor Vehicle Taxpayer registered at SAMSAT UPT Revenue scope of Regional Income Board of South Sulawesi Province. The sample in this research is determined by 100 taxpayers of Motor Vehicle Tax by using accidental sampling technique. The data was processed using SPSS version 22. The results of this study indicate that the Tax Sanctions have a positive and significant effect on the Deterrent Effects of Taxpayers, the Control of the PKB has a positive and significant effect on the deterrent effect of Taxpayer, Tax sanction with the Taxpayer character in relation to the PKB Compulsory Effect has positive and insignificant effect, PKB with the character of Taxpayers in relation to the Effects Deterrent PKB PKB positive and insignificant.